Disasters : a sociological approach - Tierney, Kathleen J. (Polity, 2019)
Disasters kill, maim, and generate increasingly large economic losses. But they do not wreak their damage equally across populations, and every disaster has social dimensions at its very core. This important book sheds light on the social conditions and on the global, national, and local processes that produce disasters.